Ion exchange resins for tartarestabilization: impacto on Rose wine quality - Borges, Rita (2020)
Tartaric acid is the most important organic acid in the wine. It is easily ionized, leading to the formation of precipitates like potassium hydrogen tartrate (KHT) and calcium tartrate (CaT). Although, not harmful to health of the consumer, these precipitates, leads to a decrease in the commercial acceptance and consequently to the decrease of the commercial value of the wine. To prevent the occurrence of these precipitations several treatments can be used. Among them, ion exchange resins is an accepted stabilization process by the OIV according to the Resolution 43/2000, as well as the treatment with oenological products such as metatartaric acid, since 1970, and carboxymetilcelulose (CMC’s), since 2009. Therefore, the aim of this work was to compare the impact of ion exchange resins with oenological additives, such as CMC’s with different structural features and metatartaric acid, on wine quality. For this propose, Douro Valley wines treated with ion exchange resins, CMC and metatartaric acid were evaluated concerning there physicochemical (phenolic compounds, chromatic characteristics, mineral composition and phenolic profile by HPLC-DAD) and sensory characteristics. Results shown that, white wine treated with ion exchange resins, presented lower concentration of total phenolic compounds compared to treated wines with oenological additives